Comparison of live donor pre‐transplant and recipient post‐transplant renal volumes. Issue 5 (29th March 2016) - Yanishi, Masaaki; Kinoshita, Hidefumi; Yoshida, Takashi; Takayasu, Kenta; Yoshida, Kenji; Mishima, Takao; Sugi, Motohiko; Tsukaguchi, Hiroyasu; Kawa, Gen; Matsuda, Tadashi
Abstract: Background: Live donor pre‐transplant and recipient post‐transplant kidney volumes based on three‐dimensional computed tomography (3DCT) have been related to post‐transplant renal function. We examined this association and the effect of sex/size differences between donor and recipient on kidney growth rate. Methods: We retrospectively reviewed 30 live donors who underwent pre‐transplant and post‐transplant 3DCT. We determined donor (Dvol) and recipient renal volumes (Rvol) based on 3DCT and calculated changes in graft volume after transplantation (Vol‐ratio). We also divided Dvol by recipient body weight (Dvol/RWgt) and compared the correlations between Vol‐ratio and Dvol/RWgt and post‐transplant renal function after one yr. We determined the rates of change in kidney volume and renal function according to the sexes of the donor and recipient. Results: The mean Dvol and Rvol were 141.7 and 178.4 mL, respectively. The mean Vol‐ratio was 127.3%. Dvol/RWgt showed a significant linear correlation with remaining renal function after one yr ( r = 0.6745, p < 0.0001). The combination of female donor and male recipient resulted in the fastest increase in kidney volume (p < 0.001) and highest level of proteinuria (p < 0.001). Conclusions: Pre‐transplant and post‐transplant kidney volumes are correlated with post‐transplant graft function, and graft growth is affected by the relative sexes of the recipient and donor.